2023
DOI: 10.3390/systems11020088
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping Analysis of Intelligent Ports: Research Facing Global Value Chain Challenges

Abstract: Integrated technology management in building smart ports or intelligent ports is a crucial concern for global sustainable development, especially when human societies are facing increasing risks from climate change, sea-levels rising, and supply chain disruptions. By mapping the knowledge base of 103 papers on intelligent ports, retrieved in late December 2022 from the Web of Science, this study conducted a roadmapping exercise using knowledge mapping findings, assisted by Bibliometrix, VoSviewer, and customiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
0
6
0
5
Order By: Relevance
“…También, su implementación en los puertos es la clave para impulsar la competitividad en la industria marítima, ya que, al aprovechar tecnologías como los vehículos guiados automatizados y las grúas de muelle, se establecen las bases para la revolución del Internet de las Cosas (IoT) en los puertos inteligentes y de cómo la automatización junto a la integración de dispositivos inteligentes pueden ser una mejora general en la cadena de suministro marítima [12]. Su aplicación para el manejo de contenedores en terminales portuarios también es crucial en la eficiencia y productividad de la cadena de suministro, mejora la conexión inalámbrica a los vehículos de guiado automático (AGV), además de que permite una transferencia eficiente de contenedores desde el barco hasta las grúas de tierra en las yardas de carga ayudando a reducir los tiempos de espera, los errores humanos y los costos operativos [11].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…También, su implementación en los puertos es la clave para impulsar la competitividad en la industria marítima, ya que, al aprovechar tecnologías como los vehículos guiados automatizados y las grúas de muelle, se establecen las bases para la revolución del Internet de las Cosas (IoT) en los puertos inteligentes y de cómo la automatización junto a la integración de dispositivos inteligentes pueden ser una mejora general en la cadena de suministro marítima [12]. Su aplicación para el manejo de contenedores en terminales portuarios también es crucial en la eficiencia y productividad de la cadena de suministro, mejora la conexión inalámbrica a los vehículos de guiado automático (AGV), además de que permite una transferencia eficiente de contenedores desde el barco hasta las grúas de tierra en las yardas de carga ayudando a reducir los tiempos de espera, los errores humanos y los costos operativos [11].…”
Section: Resultsunclassified
“…En cuanto a los resultados de la integración de la tecnología con las prácticas de la Industria 4.0, en la gestión de la construcción de puertos inteligentes puede conducir al desarrollo sostenible global; además, el desarrollo portuario que incluye la logística portuaria también puede usar el mapeo de rutas para explorar cómo las tecnologías digitales impactan en su evolución de las cadenas de valor globales, rendimiento como reducir el tiempo de respuesta sin perder su competitividad y tomar decisiones o estrategias en tiempo real a corto o largo plazo [12]. También, la digitalización puede proporcionar una conectividad más amplia y rápida entre toda la cadena logística marítima que no solo mejorará la eficiencia de la terminal, sino que también protegerá a los trabajadores de primera línea en el mar o en tierra mediante la aplicación de Internet de las cosas, inteligencia artificial, red 5G y blockchain en puertos; por ejemplo, a través de sensores es posible monitorear en tiempo real los componentes o verificar el estado de los equipos que ayudarán en el futuro entorno post pandemia a lograr objetivos financieros o no financieros [16].…”
Section: Resultsunclassified
“…The study revealed a remarkable 90.4% enhancement in reducing truck waiting times. Consequently, the adoption of Industry 4.0 technologies emerges as an indispensable strategy for the efficient control, improvement, and forecasting of port logistics Liao et al [3] start with the importance of technological management in smart ports to address the risks associated with climate change, rising sea levels, and disruptions in the supply chain, to establish the need for aligning digital transformation with the interests of the stakeholders in the process. Similarly, the results of the conceptual analysis demonstrated the existence of certain established and emerging research groups, such as the data industry, IoT, Industry 4.0, smart airports, automation, and protocol and security.…”
Section: ) Branch 1: Smart Ports: a Technological Necessity For The 2...mentioning
confidence: 99%
“…For instance, one seminal study emphasizes the necessity of forging an ecosystem of innovation and technology focused on the sustainable development of smart ports. The study advocates for the integration of Industry 4.0 technologies like the Internet of Things (IoT), Big Data, 5G, and Artificial Intelligence (AI) to align with the strategic objectives of value creation [3]. Another literature review by Bousdekis et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature indicates that the formulation of the digital transformation strategy requires the outlining of the port's enduring vision for digital transformation, along with the precise measures that will be implemented to realize that vision (Liao;It;Pan, 2023). It is imperative that the strategy is congruent with the overall resilience objectives of the port and should be based on a pragmatic assessment of the port's existing digital capacities and available resources.…”
Section: E) Establish a Governance Structurementioning
confidence: 99%